Seroprevalence of anti-HEV and HEV RNA among volunteer blood donors and patients with Hepatitis B and C in Iran - Keyvani, Hossein; Shamabadi, Mahmood Shamsi; Najafifard, Saeed; Hajibeigi, Bashir; Fallahian, Farahnaz; Alavian, Seyed-Moayed (Bangladesh Liver Journal, 2009)
Aim: To assess seroprevalence of antibodies to hepatitis E virus (HEV) in healthy blood donors and hepatitis B, C patients. Methods: 450 subjects consisted of 200 blood donors in Tehran blood transfusion center, 100 subjects with hepatitis C and 150 subjects with hepatitis B infection enrolled in this study. The A549 cell line was grown in mixed medium. Cells were infected with hepatitis E virus that was purified from stool sample of a patient confirmed for hepatitis E infection by reverse transcription-polymerase chain reaction (RT-PCR) method. Supernatant of infected cells was used as positive control in our RT- PCR assay. Results: In a total of 450 subjects, 33 (7.3%) had positive anti-HEV by enzyme-linked immunosorbent assay (ELISA). Anti-HEV was seen in (9/200) 4.5%, (7/100) 7%, and (17/150) 11.3% of healthy blood donors, hepatitis C, and hepatitis B subjects, respectively. Difference between two groups was statistically significance (P = 0.028). Difference between frequency of anti-HEV in hepatitis B in relation to healthy blood donors was significant (P = 0.014). Conclusions: HEV infection is more common in subjects with hepatitis B. Keywords: Hepatitis E virus, Seroprevalence, Transmission, Iran doi: 10.3329/blj.v1i1.2623 Bangladesh Liver Journal Vol.1(1) 2009 p.34-37